Imagens em estudo: os autorretratos na internet e na arte contemporânea - Zambianchi, Paola Basile da Silva (2012)
This research intends to analyze the imagistic autobiographies representations operated by the image publishing website called fotolog, as parameter of the analysis, the art, specifically the contemporary self-portraits. Therefore, we examined in this paper, the extent to which reality and fiction blend in the production of this identities; and how the resources of art, specifically the image, are used to construct these self-portraits. Overexposure and theatricality are also common features between the two media and will be discussed in the survey. To map the similarities between the virtual identities on the web and the self-portraits of contemporary art we define, as a starting point for this discussion, the fotolog sensationslave and artwork of French Sophie Calle.